If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 72 = -23x Reorder the terms: 72 + 13x = -23x Solving 72 + 13x = -23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23x' to each side of the equation. 72 + 13x + 23x = -23x + 23x Combine like terms: 13x + 23x = 36x 72 + 36x = -23x + 23x Combine like terms: -23x + 23x = 0 72 + 36x = 0 Add '-72' to each side of the equation. 72 + -72 + 36x = 0 + -72 Combine like terms: 72 + -72 = 0 0 + 36x = 0 + -72 36x = 0 + -72 Combine like terms: 0 + -72 = -72 36x = -72 Divide each side by '36'. x = -2 Simplifying x = -2
| p-24=19/6(18-5) | | 6x+5/x-3+x-6/3x-9 | | 4y=5y-2 | | -7x-5(-4x-11)=-101 | | 10+2x-2x=0 | | 4+2x=36 | | 6x+12=9x+17 | | p-24=19/6(h-5) | | -20+24x+9x^2=0 | | 4x^3-12X^2+20X=0 | | x+5-3x=2x+8-5x | | -4x-3(4x-2)=-86 | | 3(x+1)-4(2x-5)+10x= | | 5X+(X-3)=X-(2X+5) | | f(x)=x^2(6-x) | | 3/4(12x+32)=99 | | -49/7 | | 3+9x=57 | | -175-30x+x^2=0 | | -6x-2=-1x+3 | | (7+2I)-(3-4i)=0 | | 5x+6=48 | | 7n-(3n+8)= | | ((2x^6)/(x^4))((x^2+4x+4)/(4x^7)) | | 7b-(3b+8)= | | 5x+4=74 | | 9(x+2)=58 | | -8+10x+25x^2=0 | | 16-2(3x-1)=12-1(4-8x) | | -2x=-1-y | | -4x^2+5x=1 | | 4x-4=4(x+1) |